الأسلوب الشعري عند كعب بن زهير ودوره في أسلمة المعرفة: شعر الإسلامية أنموذجا: The Poetic Style of Ka`b bin Zuhair and Its Role in the Islamization of Knowledge: Islamic Poetry as a Model - Abd Rahman, Siti Hazwani; Ahmad H. Osman, Rahmah; Zaina, Muhammad Asyraf (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص كعب بن زهير له مكانة عالية في الشعر العربي وهو سليل عائلة موهوبة بالشعر، فأبوه الشاعر الجاهلي المعروف زهير بن أبي سلمى، كان هو من الشعراء المشهورين في الجاهلية حتى بعد ظهور الإسلام. وقد لعب كعب بن زهير دورا مهما في الحفاظ على رسالة الإسلام من خلال أشعاره وقصائده.فهناك الكثير من القيم الإسلامية والمعرفة عن الإسلام تظهر من خلال شعر كعب بن زهير في عصر الإسلام. وتهدف هذا الدراسة إلى معرفة الأسلوب الشعري عند كعب بن زهير في شعره الإسلامي واكتشاف دوره في أسلمة المعرفة عن طريق شعره. وقد اعتمدت المقالة على المنهج الوصفي المكتبي وركز البحث في الشعر الإسلامي. وقام الباحثان بتحليل الشعر الإسلامي لكعب بن زهير اعتمادا على شرح ديوان كعب بن زهير لأبي سعيد الحسين بن الحسين بن عبد الله السكرى. وتوصلت الدراسة إلى أن شعر كعب بن زهير تأثر بالإسلام من حيث المصطلحات والأساليب تأثرا عميقا. Abstract Kaab bin Zuhair has a high status in Arabic poetry and is a descendant of a family gifted with poetry. His father is the well-known pre-Islamic poet Zuhair bin Abi Salma. He was one of the famous poets in the pre-Islamic era even after the advent of Islam. It is worth noting that he plays an important role in preserving the message of Islam through his poems and poems. Likewise, there are many Islamic values and knowledge about Islam from the poetry of Ka`b bin Zuhair in the era of Islam. This research aims to know the poetic style of Kaab bin Zuhair in his Islamic poetry and to discover a role in his poetry about the Islamization of knowledge. The article released on the desk descriptive approach and focused the research on Islamic poetry. The researcher analyzed the Islamic poetry of Kaab bin Zuhair based on the explanation of the Diwan of Kaab bin Zuhair to Abu Saeed Al Hussein bin Al Hussein bin Abdullah Al Sukari. The research concluded that Kaab bin Zuhair's poetry was profoundly affected by Islam in terms of terms and methods.